2004
DOI: 10.1128/iai.72.5.2507-2512.2004
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Immunization with Multivalent Group A Streptococcal Vaccines Protects Mice against Intranasal Challenge Infections

Abstract: We have previously shown that a hexavalent group A streptococcal M protein-based vaccine evoked bactericidal antibodies after intramuscular injection. In the present study, we show that the hexavalent vaccine formulated with several different mucosal adjuvants and delivered intranasally induced serum and salivary antibodies that protected mice from intranasal challenge infections with virulent group A streptococci. The hexavalent vaccine was formulated with liposomes with or without monophosphorylated lipid A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 20 publications
1
51
0
Order By: Relevance
“…Several recent M-protein-based studies have investigated the protective efficacy of the N-terminal hypervariable region (338,444,(534)(535)(536)(537)(538)(539), as this region may not be involved in autoimmune disease. Two N-terminal M protein vaccine preparations have reached human clinical trials to date: a hexavalent preparation (444,539,540) and a 26-valent preparation (541,542). These preparations were well tolerated in adult volunteers.…”
Section: M-protein-based Vaccine Preparationsmentioning
confidence: 99%
“…Several recent M-protein-based studies have investigated the protective efficacy of the N-terminal hypervariable region (338,444,(534)(535)(536)(537)(538)(539), as this region may not be involved in autoimmune disease. Two N-terminal M protein vaccine preparations have reached human clinical trials to date: a hexavalent preparation (444,539,540) and a 26-valent preparation (541,542). These preparations were well tolerated in adult volunteers.…”
Section: M-protein-based Vaccine Preparationsmentioning
confidence: 99%
“…Hence, a vaccine targeting this highly variable region of M protein needs to be multivalent, consisting of several types. Currently, such multivalent vaccines composed of the most common emm types in Australia and United States are in development (9,20,23).…”
mentioning
confidence: 99%
“…The serum antibody titer after 3 immunizations was similar to that obtained with multivalent fusion protein vaccines (20)(21)(22). Although we did not determine mucosal levels of IgA in saliva, we were unable to recover GAS from the oropharynx of vaccinated mice, suggesting that immunization impacted GAS colonization or infection at the level of the mucosa.…”
Section: Discussionmentioning
confidence: 67%
“…In fact, clinical and microbiological responses to Streptococcus gordonii, a commensal LAB, have already been assessed in healthy volunteers, which demonstrated that its use as a live mucosal vaccine vector is feasible (27). LAB vaccines can be administered intranasally, which may prove to be the optimal immunization route for a GAS vaccine (20,28). The vaccine candidate presented here can be produced inexpensively and easily delivered without the need for a syringe or highly skilled personnel.…”
Section: Discussionmentioning
confidence: 99%